The Role Of Financial Literacy In Household Financial Decision-Making In Emerging Economies - Anirudh Sinha; Priya Chandrasekhar; Megha Kapoor (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study explores the importance of financial literacy in influencing household financial decisions in emerging economies. Using survey data from multiple regions, the research examines how knowledge of financial concepts affects budgeting, saving, and investment choices. The results indicate that higher financial literacy levels are strongly linked to more effective financial management and improved economic well-being among households.